Respuesta :

Answer:

3x + 10

Step-by-step explanation:

9 + x + 1 + 2x

Combine like terms

2x + x = 3x

Combine like terms

9 + 1 = 10

We’re left with 3x + 10

[tex]\huge\text{Hey there!}[/tex]

[tex]\huge\text{9 + x + 1 + 2x}[/tex]

[tex]\huge\text{= 9 + 1x + 1 + 2x}[/tex]

[tex]\huge\textsf{COMBINE the LIKE TERMS}[/tex]

[tex]\huge\text{= (9 + 1) + (1x + 2x)}[/tex]

[tex]\huge\text{= 10 + 3x or 3x + 10}[/tex]

[tex]\huge\text{Answer: \textsf{3x + 10}}[/tex]

[tex]\huge\text{Good luck on your assignment \& enjoy your day!}[/tex]

~[tex]\frak{Amphitrite1040:)}[/tex]